Adaptação transcultural e validação de instrumento de avaliação da atuação do tutor no grupo tutorial na Aprendizagem Baseada em Problemas - Sales Filho, Eisenhower Pego de (2020)
Introduction: With a better understanding of adult learning and human memory, active learning methods have increased medical curricula' prominence. Among these methods, problem-based learning (PBL) stands out, in which the tutor has an essential role, serving as a learning facilitator. It has been a matter of controversy in the literature if the differences in acting and the different tutors' profiles could affect their performance and the reflection in PBL. In this context, it is necessary to measure, through reliable instruments, the tutor's performance, from the student's point of view, to subsidize educational interventions with a potentially positive impact on students' training. The Revised University of Sidney Medical Program PBL Tutor Feedback Form questionnaire is concise, self-applied, fast application, and can bring important information. Objective: Perform translation, cross-cultural adaptation, and validation of the Revised University of Sydney Medical Program PBL Tutor Feedback Form questionnaire to assess the perception of tutor performance in PBL. Methodology: The stages of translation, synthesis, back-translation, review by a group of experts, and pre-test of the questionnaire occurrence, followed by assessing the validity of internal consistency of the data and psychometric analysis of the data. Posteriorly we developed Two versions of the instrument based on the original questionnaire. One adapted to the primary cycle, in which we removed questions related to clinical problems. The other, specific for students from the clinical process, was similar to the original, covering all items. Result: 367 students participated in the study, 118 from the second period, 116 from the third, 56 from the sixth, and 77 from the seventh. The questionnaire's internal consistency, assessed by Cronbach's alpha test, was 0.924 for the primary cycle instrument and 0.950 for the clinical cycle instrument. The basic cycle apparatus comprises 14 items with a score between 14 and 70 and the general assessment item, and three open answer items. The clinical cycle instrument has 21 items assessed on a “Likert” scale with scores ranging from 21 to 105, one general assessment item, and three open-response items. As we maintained the fields, it is possible to compare primary and clinical cycles. The Cronbach’s alpha of the original domains was satisfactory in all parts, both instruments in individual analysis. Conclusion: The questionnaire was considered valid and made available for use in the Brazilian Portuguese language, being useful to assess the student's perception of the tutor in the PBL method